Austenitic Stainless Steels - New Aspects 2017
DOI: 10.5772/intechopen.70558
|View full text |Cite
|
Sign up to set email alerts
|

Friction Welding of Austenitic Stainless Steel with Copper Material

Abstract: Austenitic stainless steels are most preferred over other types of stainless steel families. Welding of stainless steel using friction welding is widely seen in the current scenario. Since the time consumed for friction welding is very less, metallurgical defects are almost reduced without pre-and postheat treatment. The problems encountered in friction welding during joining of austenitic stainless steel are very limited when compared to fusion welding process. The studies have undergone with joining of auste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
1
5
1
Order By: Relevance
“…Hardness analysis also indicated that the fracture propagates through the heat affected zone (HAZ) along the copper base-metal. A similar hardness gradient along both the sides of the interfacial region was reported in some other works published [ 97 , 98 , 100 , 106 , 107 , 108 ]. This clearly indicates limited atomic mobility along both sides of the interfaces for FW procedure compared to other solid-state welding processes such as HIP and DB.…”
Section: Solid-state Welding Of Copper/stainless Steel Bimetallic Jointsupporting
confidence: 87%
See 3 more Smart Citations
“…Hardness analysis also indicated that the fracture propagates through the heat affected zone (HAZ) along the copper base-metal. A similar hardness gradient along both the sides of the interfacial region was reported in some other works published [ 97 , 98 , 100 , 106 , 107 , 108 ]. This clearly indicates limited atomic mobility along both sides of the interfaces for FW procedure compared to other solid-state welding processes such as HIP and DB.…”
Section: Solid-state Welding Of Copper/stainless Steel Bimetallic Jointsupporting
confidence: 87%
“…Researchers have explored friction welding (FW) to join the dissimilar metals, but limited their investigation to pipe joints [ 160 , 161 , 162 , 163 ]. FW has shown significant potential to join copper with stainless steel [ 105 , 106 , 107 , 108 ]. Joint integrity mainly depends upon the formation of intermetallic along the interfaces.…”
Section: Solid-state Welding Of Copper/stainless Steel Bimetallic Jointmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present work, the dataset is used from the research work carried out by Chinnakannan et al [9] for implementing various Machine learning classification models for determining the fracture location of dissimilar Friction Stir Welded austenitic stainless steel with the copper material.…”
Section: Introductionmentioning
confidence: 99%